TECHNOLOGY OF DEVELOPING CRITICAL THINKING IN TEACHING INFECTIOUS DISEASES IN UNIVERSITY - Rabbimova, Nodira (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
In the context of modern medical education, the development of critical thinking in students is of particular importance. This is necessary for adequate interpretation of clinical situations, interpretation of laboratory and instrumental data, as well as making scientific decisions and conditions of uncertainty. When teaching infectious diseases, which are characterized by the complexity of diagnosis, variability of the clinical picture and the need for rapid response, critical thinking becomes the most important competence of future doctors. This article examines methods and technologies aimed at developing critical thinking in medical students when studying infectious diseases.